Ocupações e Defensoria Pública: performances compartilhadas de mobilização do direito na luta por moradia no centro de Vitória - Paula, Vinicius Lamego de (2020)
ABSTRACT Occupations and Public Defender s Office: Coordinated performances of law mobilization in the struggle for housing in downtown Vitória. In April 2017, there was a large occupation in the city of Vitória, involving about 500 families. As an offsho